THE INFLUENCE OF MANAGERIAL OWNERSHIP, FIRM SIZE AND LEVERAGE ON FINANCIAL PERFORMANCE IN MINING COMPANIES - Bhifa Ayu Amelia; Wulan Suryandani (Pascasarjana Universitas Halu Oleo, 2023)
A company's financial situation is generally described by its financial performance, also as a result of various decisions that have been made by company management. The goals of this research are to investigate and demonstrate the impact of managerial ownership, company size and leverage on financial performance in mining companies in 2017-2021. The total population in mining companies is 47 companies and the companies used as the final sample are only 11 companies. Purposive sampling was the method of sampling employed in the research. Multiple linear regression analysis was the technique used in the research for data analysis. The findings indicated that managerial ownership has a positive and insignificant impact on financial performance, company size has a significant negative impact on financial performance and leverage has a significant negative impact on financial performance.